Populism’s four driving emotions, and how to cultivate emotions supporting democracy: An interview with Eva Illouz (Sociologisk Forskning, 2023)
We are delighted to present this interview with world renowned sociologist Eva Illouz. She currently holds the position of Directrice d'Etudes at the École des Hautes Études en Sciences Sociales in Paris and is the Rose Isaac Chair in Sociology at the Hebrew University of Jerusalem. Her research focuses on the interlinkages between capitalism, emotions, gender, culture, love, sexuality, and freedom in the modern world.This interview primarily centers around Illouz's latest book but also touches on the role of social media in propagating negative emotions, strategies for cultivating emotions such as fraternity and hope to sustain modern democracy, and the contemporary era marked by societal self-destruction and unprecedented catastrophes.
Keywords: emotions; populism; democracy; reflexivity